Domino Effects and Industrial Risks: Integrated Probabilistic Framework – Case of Tsunamis Effects (2013)
This paper presents an integrated probabilistic framework that deals with the industrial accidents and domino effects that may occur in an industrial plant. The particular case of tsunamis is detailed in the present paper: simplified models for the inundations depths and run-ups as well as their mechanical effects on industrial tanks. The initial accident may be caused by severe service conditions in any of the tanks either under or at atmospheric pressure, or triggered by a natural hazard such as earthquake, tsunami or extreme floods for instance. This initial event generates, in general, a set of structural fragments, a fire ball, a blast wave as well as critical losses of containment (liquid and gas release and loss). The surrounding facilities may suffer serious damages and may also be a new source of accident and explosion generating afterwards a new sequence of structural fragments, fire ball, blast wave and confinement loss. The structural fragments, the blast wave form and the features of the fire ball can be described following database and feedback collected from past accidents. The surrounding tanks might be under or at atmospheric pressure, and might be buried or not, or protected by physical barriers such as walls. The vulnerability of the potential targets should therefore be investigated in order to assess the risk of propagation of the accidents since cascading sequences of accidents, explosions and fires may take place within the industrial plant, giving rise to the domino effect that threatens any industrial plant. The present research describes the risk of domino effect occurrence. The methodology is developed so that it can be operational and valid for any industrial site. It is supposed to be valid for a set of sizes, forms and kinds of tanks as well as a given geometric disposal on the industrial site. The interaction and the behavior of the targets affected or impacted by the first explosion effects should be described thanks to adequate simplified or sophisticated mechanical models: perforation and penetration of metal fragments when they impact surrounding tanks, as well as global failure such as overturning, buckling, excessive bending or shear effects, etc. The vulnerability analysis is detailed for the case of tanks under the mechanical effects generated by tsunamis.